2021
DOI: 10.1108/sjme-12-2019-0109
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the intention to revisit a destination by expanding the theory of planned behaviour (TPB)

Abstract: Purpose The purpose of this study is to unearth the factors that influence tourists’ revisit intention. The proposed model of the study is grounded on using the theory of planned behaviour (TPB) and extending it with additional variables, i.e. satisfaction, destination image, perceived risk, service quality and perceived value. Design/methodology/approach This study adopted a cross-sectional approach to collect data. The data were collected by conducting a field survey questionnaire on 330 respondents and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
187
6
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(231 citation statements)
references
References 122 publications
(195 reference statements)
29
187
6
9
Order By: Relevance
“…Intention to visit has been considered as a major determinant of growth and survival of the tourism business because it helps in forecasting marketing expenses ( Kim et al, 2013 ), profitability ( Alves et al, 2019 ), and sustainability of tourism business ( Stylos et al, 2017 ). Furthermore, the trade-off between attracting and retaining the costs of tourists determines the competitive advantage ( Chiu et al, 2012 ; Kim et al, 2013 ; Abbasi et al, 2021 ), which is also a function of tourists visit intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Intention to visit has been considered as a major determinant of growth and survival of the tourism business because it helps in forecasting marketing expenses ( Kim et al, 2013 ), profitability ( Alves et al, 2019 ), and sustainability of tourism business ( Stylos et al, 2017 ). Furthermore, the trade-off between attracting and retaining the costs of tourists determines the competitive advantage ( Chiu et al, 2012 ; Kim et al, 2013 ; Abbasi et al, 2021 ), which is also a function of tourists visit intentions.…”
Section: Introductionmentioning
confidence: 99%
“…In the tourism industry, the factors that influence tourists to revisit include satisfaction, attractiveness, accommodation, service, culture, risk [4]. [5] suggested that the factors that influence the intention of returning tourists include perceived behavioral control, perceived value, destination image and satisfaction. Meanwhile, [6] prove that country image and destination image influence revisit intention via the mediating effect of memorable tourist experience.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of reasoned action [54], just like the theory of planned behavior [54], aims to predict the behavior of individuals or to understand how a behavior can evolve or change. Indeed, for the authors of these models, it is intention that constitutes the determining factor of behavior [55,56]. The stronger the intention, the more effort the person will put into this behavior and the more likely they are to engage in this behavior.…”
Section: Theory Of Reasoned Action and The Theory Of Planned Behaviormentioning
confidence: 99%
“…This behavioral control can be influenced by past experiences but also by anticipated obstacles. This variable can influence the onset of behavior in direct or indirect ways [55]. Thus, even if an individual has a favorable attitude towards a behavior and his entourage approves this behavior, he will not develop an intention to act if he does not believe that he has the necessary resources (time, money, skills, etc.)…”
Section: Theory Of Reasoned Action and The Theory Of Planned Behaviormentioning
confidence: 99%
See 1 more Smart Citation